Seed Size Variation and its Effect on Germination and Seedling Growth of Jatropha curcas L. - Singh, Nidhi; Saxena, A. K. (Indian Forester, 2009)
Jatropha curcas was evaluated for its seed size variability and effect of seed size on germination, seedling growth and dry weight. Among the three seed size classes viz. small (13-15 mm), medium (15-17 mm) and large (17-19 mm), maximum proportion of seeds by number (62%) and dry weight (63%) was recorded in the medium seed size class. Germination and related parameters were positively correlated with seed size in laboratory as well as in nursery conditions. Large seeds showed remarkable increment in germination per cent (50%), germination value (210%), germination speed (100%) and germination energy (72%) over the small seeds in the laboratory. This increment in germination and related parameters for large seeds over the small seeds was even greater in nursery condition. Significant variations due to seed size were also observed for the growth and dry weight of J. curcas seedlings. Seed size showed a positive relation with growth and dry weight of seedling. Maximum height, collar diameter, number of leaves and total dry weight was found in the seedlings raised from large seeds, hence large seeds of J. curcas should be preferred to get better and uniform germination and quality seedlings.